2019
DOI: 10.3847/1538-4357/ab2a75
|View full text |Cite
|
Sign up to set email alerts
|

Determining Electron Temperature and Density in a H ii Region Using the Relative Strengths of Hydrogen Radio Recombination Lines

Abstract: We have introduced a new method of estimating the electron temperature and density of H II regions by using single dish observations. In this method, multiple hydrogen radio recombination lines of different bands are computed under the assumption of low optical depth. We use evolutionary hydrodynamical models of H II regions to model hydrogen recombination line emission from a variety of H II regions and assess the reliability of the method. According to the simulated results, the error of the estimated temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Higher electron temperature will lead to higher free-free emission contributions. The electron temperature could be better constrained by observing multiple RRLs in future (Zhu et al 2019). We found that the 3 mm continuum emission in "B", "MM1/C" and "MM11/D" is dominated by free-free emission, as suggested in previous works (Hofner et al 1996).…”
Section: Filaments and Dense Coressupporting
confidence: 78%
“…Higher electron temperature will lead to higher free-free emission contributions. The electron temperature could be better constrained by observing multiple RRLs in future (Zhu et al 2019). We found that the 3 mm continuum emission in "B", "MM1/C" and "MM11/D" is dominated by free-free emission, as suggested in previous works (Hofner et al 1996).…”
Section: Filaments and Dense Coressupporting
confidence: 78%
“…The oscillator strength can be calculated more accurately from the method described in Brocklehurst (1971) and Regemorter & Prudhomme (1979). The accurate values have been used in recent models of Prozesky & Smits (2018) and Zhu et al (2019Zhu et al ( , 2022. The modeled spectrum in this work will not change obviously when the more accurate values of f n n , 1 2 are adopted.…”
Section: Emission Model Of Rrlsmentioning
confidence: 99%
“…If the RRL emitters are in LTE state, the departure coefficients should be unity for all levels. For n e = 10 4 cm −3 and T = 8000 K, we calculated the population of hydrogen using the method by Zhu et al (2019Zhu et al ( , 2022. The departure coefficients b n increase from 0.85-0.99 as n increases from 50-100.…”
Section: Emission Model Of Rrlsmentioning
confidence: 99%
“…Storey & Hummer (1995) included later the angular momentum l, and finally the contribution of the continuum radiation was introduced (Prozesky A. & Smits 2018, Zhu et al 2019).…”
Section: Recombination Line Maser Theorymentioning
confidence: 99%